Eight dates : essential conversations for a lifetime of love - Gottman, John Mordechai; Gottman, Julie Schwartz; Abrams, Douglas Carlton; Abrams, Rachel Carlton (Workman Publishing, 2018)
"Happily ever after is not by chance. It 's by choice. Strengthen and deepen your love with a simple and fun program of eight life-changing conversations." -- Back cover.